Transitioning to rural practice together: a rural fellowship model (in 6 Ps) - Benjamin Gilmer; Chase Harless; Lauren White Gibson; Jill Fromewick; Robyn Latessa; Gary Beck Dallaghan; Kylie Agee; Bryan Hodge (Rural and Remote Health, 2024)
Purpose: Maintaining a robust healthcare workforce in underserved rural communities continues to be a challenge. To better meet healthcare needs in rural areas, training programs must develop innovative ways to foster transition to, and integration into, these communities. Mountain Area Health Education Center designed and implemented a 12-month post-residency Rural Fellowship program to enhance placement, transition, and retention in rural North Carolina. Utilizing a '6 Ps' framework, the program targeted physicians and pharmacists completing residency with the purpose of recruiting and supporting their transition into the first year of rural practice. Method: To better understand Rural Fellows' experiences and the immediate impact of their Fellowship year, we conducted a semi-structured interview using a narrative technique and evaluated retention rates over time. Interviews with the eight participants, which included Fellowship alumni and current Fellows, demonstrated the impact and influence of the key curricular '6 Ps' framework. Results: An early retention rate of 100% and a long-term retention rate of 87%, combined with expressed clarity of curricular knowledge, skills, and attitudes related to the '6 Ps', demonstrate the potential and effectiveness of this Rural Fellowship model. Participants indicated the Rural Fellowship experience supports the transition to rural practice communities and expands their clinical skills. Conclusion: The Rural Fellowship program demonstrates an effective model to support early career healthcare providers as they begin practice in rural communities in western North Carolina through academic opportunities, personal growth, and professional development. Implementation of this model has demonstrated the success of a rural retention model over a 6-year period. This model has the potential to target an array of clinical providers and disciplines. We started with family medicine and have expanded to psychiatry, obstetrics, pharmacy, and nursing. This study demonstrated that this model supports clinical providers during the critical transition period from residency to practice. Targeting the most important stage of one's medical training, the commencement of professional practice, this is a scalable model for other rural-based health professions education sites where rural recruitment and retention remain a problem.